Sosialisasi Mekanisme Gugatan Sederhana Pada UMKM di Desa Girisekar, Kecamatan Panggang, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta - Fakultas Hukum Universitas Negeri Surabaya; Ahmad Mubaroq; Alfan Nurrachman; Emmilia Rusdiana (Fakultas Hukum, Universitas Negeri Surabaya, 2025)
Breach of contract and unlawful acts are recurring issues within business sectors, especially affecting micro, small, and medium enterprises (MSMEs). Despite legal avenues available, many MSME actors hesitate to seek judicial remedies due to perceptions of lengthy, costly, and ineffective litigation. To address this, the Community Service Team of Universitas Negeri Surabaya conducted a socialization program introducing the Small Claims Court mechanism. This initiative aimed to provide MSME actors with an alternative legal resolution that is faster, simpler, and more cost-effective. The program focused on disputes commonly faced by MSMEs, such as contract breaches and torts, which are usually resolved informally. Through workshops in Girisekar Village, participants gained knowledge of legal procedures and the state-guaranteed legal aid available for MSMEs. Most had never encountered the small claims mechanism prior to the program. The activity not only raised awareness but also reduced stigma against litigation by simplifying the concept of access to justice. Additionally, recommendations were given to local governments, particularly village officials, to create supportive policies and legal assistance for MSMEs. The initiative successfully fostered legal empowerment and encouraged a more just legal culture among small business communities.